Influence of applied potential on bradykinin adsorption onto Ag, Au, and Cu electrodes. (29th January 2013) - Proniewicz, Edyta; Skołuba, Dominika; Ignatjev, Ilja; Niaura, Gediminas; Sobolewski, Dariusz; Prahl, Adam; Proniewicz, Leonard M.
<x xml:space="preserve">Abstract</x> Surface‐enhanced Raman scattering, electrochemistry, and generalized two‐dimensional correlation analysis (G2DCA) methods were used to characterize bradykinin (BK), a hormone which is known to be involved in small‐cell and non‐small‐cell lung carcinoma and prostate cancer. BK was deposited onto Ag, Au, and Cu electrode surfaces under different applied electrode potentials (−1.000 V to 0.200 V) in aqueous solutions. Based on the analysis of the enhancement, the broadening, and the shifts in the wavenumbers of individual bands, specific conclusions were drawn regarding the peptide geometry and changes in this geometry that occurred when the electrode type and applied electrode potential were varied. Briefly, BK deposited onto the Ag, Au, and Cu electrode surfaces showed bands that were due to the vibrations of moieties in contact with or in close proximity to the electrode surfaces and were thus located on the same side of the polypeptide backbone. These moieties included the Phe, Arg, and Pro residues. The findings for adsorbed BK were fully supported by G2DCA, which also allowed us to determine the order in which changes occurred when the electrode potential was changed. In addition, it was found that at negative electrode potentials, the Phe rings and methylene groups interact with Ag electrode surface. No such interaction was observed for Au and Cu electrodes. Copyright © 2013 John Wiley & Sons, Ltd.